2003
DOI: 10.1097/00002826-200301000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effect of Donepezil Augmentation for the Management of Comorbid Schizophrenia and Dementia

Abstract: Comorbid schizophrenia and dementia is a common clinical phenomenon; however, management of the coexisting illnesses remains incomplete. Donepezil, a cholinesterase inhibitor, may be beneficial for the management of symptoms of Alzheimer's disease, a disease in which cholinergic pathways in the cerebral cortex and basal forebrain are well known to be compromised. Furthermore, impaired cognition in elderly schizophrenic patients has been observed to be more than two thirds; however, there are no published contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…To date, however, the data collected in the relatively small number of clinical studies that have been designed to evaluate the potential cognitive benefits of AChEIs in schizophrenia have been equivocal. For example, the beneficial effects of donepezil or rivastigmine on cognition in schizophrenics as add-on treatments to antipsychotics observed in small preliminary investigations, open-label studies and case reports (e.g., Buchanan et al, 2003;Stryjer et al, 2003;Lenzi et al, 2003) were not confirmed in larger randomized, doubleblind, and placebo controlled studies (see Friedman et al, 2002;Freudenreich et al, 2005;Sharma et al, 2006). In the case of galantamine, there are also several small studies that indicate a potential benefit to schizophrenic patients including a recent randomized, doubleblind clinical trial (N=8) where the AChEI improved short-term memory and attention in schizophrenic or schizoaffective patients who were stabilized on risperidone (Schubert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To date, however, the data collected in the relatively small number of clinical studies that have been designed to evaluate the potential cognitive benefits of AChEIs in schizophrenia have been equivocal. For example, the beneficial effects of donepezil or rivastigmine on cognition in schizophrenics as add-on treatments to antipsychotics observed in small preliminary investigations, open-label studies and case reports (e.g., Buchanan et al, 2003;Stryjer et al, 2003;Lenzi et al, 2003) were not confirmed in larger randomized, doubleblind, and placebo controlled studies (see Friedman et al, 2002;Freudenreich et al, 2005;Sharma et al, 2006). In the case of galantamine, there are also several small studies that indicate a potential benefit to schizophrenic patients including a recent randomized, doubleblind clinical trial (N=8) where the AChEI improved short-term memory and attention in schizophrenic or schizoaffective patients who were stabilized on risperidone (Schubert et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In two open-label trials where donepezil was added to the ongoing treatment of schizophrenia subjects with atypical antipsychotic drugs, an improvement in manual dexterity (Buchanan et al, 2002) and in clinical measures of dementia (eg MMSE) (Stryjer et al, 2003) was observed. However, in double-blind studies of donepezil added to treatment with risperidone (Friedman et al, 2002) or clozapine (Stryjer et al, 2004), no beneficial effects were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of donepezil (5 mg) to the standard antipsychotic treatment in a small cohort of elderly subjects with schizophrenia was shown to cause a modest improvement in cognitive measurements. 125 In a subsequent study, the addition of donepezil to clozapine in a double-blind crossover design showed no overall effect. Still, three out of eight subjects improved in the total Positive and Negative Syndrome Scale-score during the donepezilphase.…”
Section: Use Of Cholinesterase Inhibitors In Schizophreniamentioning
confidence: 95%